THE IMPLEMENTATION OF VISUAL MEDIA AND GAMES IN IMPROVING THE STUDENTS’ VOCABULARY AT ELEVENTH GRADE OF SMA NEGERI 1 SECANGGANG - Nurlaini; Arsen Nahum Pasaribu; Erika Sinambela (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2026)
This research was “The implementation of visual media and games in improving the students’ vocabulary at eleventh grade of SMA Negeri 1 Secanggang”. It consisted of two problem statements. They were (1) How was the implementation of Visual Media and Games in improving the students’ vocabulary of second year students’ at SMA Negeri 1 Secanggang? (2) How was the improvement of students’ vocabulary through Visual Media and Games of second year students’ at SMA Negeri 1 Secanggang? The objective of this research was to find out improvement of the students’ vocabulary by visual media and games of XI IPA 4 at SMA Negeri 1 Secanggang. This research was classroom action research. It consisted of two cycles. The procedure of the research in every cycle consisted of four stages. They were planning, acting, observing, and reflecting. The subject of the research consisted of 40 students of XI IPA 4 at SMA Negeri 1 Secanggang. The instruments of this research were test which was analyzed by quantitative analysis and observation sheet which was analyzed by qualitative analysis. The result of the research showed that there was a significant improvement of the students’ vocabulary after using visual media and games. This statement could prove by the students’ mean score of ability test was 6.33, but it had increased to 6.80 the first cycle and 7.51 at the second cycle. It means that the students’ vocabulary from the first cycle to second cycle was classified successful. Visual media and Games could improve the students’ vocabulary.